Control of ferromagnetism in (In0.9Fe0.1)2O3 via F doping of electron carriers. (January 2015) - Yan, Shiming; Ou, Haifeng; Zhang, Liying; He, Jie; Yu, Jingxin
Graphical abstract: Highlights: F doping was achieved by a process of low temperature reaction with PVDF. RTFM was obtained in the F-doped (In0.9 Fe0.1 )2 O3. Magnetism and electric resistivity can be controlled by the content of doped F. The FM can be ascribed to a long range exchange interaction induced by carriers. Abstract: Ferromagnetism in (In0.9 Fe0.1 )2 O3 was obtained by fluorine (F) doping. The ferromagnetism can be controlled by changing the electron carrier concentration via F doping. With increasing the F concentration, the electron carrier concentration increases, and samples undergo a paramagnetic insulator to ferromagnetic metal transition. For the ferromagnetic samples, the anomalous Hall effect (AHE) was observed. These results indicate that electron carriers play an important role in inducing the ferromagnetism.